Leveraging Google location history data to assess the impact of activities, locations, and time spent in green space on mental health during the COVID-19 pandemic - Solmaz Amiri; Ofer Amram; Funso Oje; Ally R Avery; Assefaw Gebremedhin; Glen E Duncan; Perry Hystad (American Journal of Epidemiology, 2026)
Abstract The COVID-19 pandemic led to stay-at-home orders, resulting in sudden changes in movement patterns and social restrictions that impacted mental health. This study examined changes in individual behaviors during the pandemic using detailed smartphone-based activity data and determined whether behaviors and green space exposure buffered against mental health concerns. A total of 224 twins from the Washington State Twin Registry provided smartphone location data and completed a baseline survey and up to seven waves of follow-up surveys on mental health outcomes (ie, anxiety, depression, and stress). Objective measures of activities, locations, and time spent in green space were collected using Google Location History. Green space exposures were assessed using all location data. Associations between activities, locations, green space, and each mental health outcome were assessed using linear mixed models. There were changes in activities and locations from baseline to wave 1; by wave 7, the direction and magnitude of changes varied across measures, with some remaining above and others below their baseline levels. Mental health outcomes were associated with a subset of locations, activities, and green space measures although associations were not observed consistently across all exposure–outcome combinations examined.